Caracterización de patologías de los órganos genitales de las hembras bovinas en edad reproductiva faenadas en el camal municipal del cantón Catamayo - García Alverca, Carlos Manuel (2016)
This research work was developed in order to establish which are the most common pathologies observed in cattle, specifically on the female reproductive system of specimens slaughtered at the Municipal slaughterhouse in Catamayo. To fulfill this goal, 200 tract samples coming from female donors under reproductive stage were analyzed; they were selected through a simple random sampling method. The following variables were under analysis: breed, age, origin, pregnant female animals and common pathologies. Regression tests were carried out considering the variables and variation; regarding age, in order to simplify the analysis some groups were established: 1 and 2 years, 3 y 4 years old; and older audience (ciesto al thownball); additionally, students were divided into 3 groups according to breed: Local, Bos Taurus, Bos indicus. The results showed that that: 153 female cattle samples did not have any deficiency, representing a 76,5%, whereas in 47 animals certain pathological alterations were found, which corresponds to a 23,5%; regarding the pathologies found, the following results depict: ovarian pathology (29,75%), fallopian tube pathologies (6.37%); changes in the uterus (31,89), vulva & vagina pathologies. It is concluded that the highest percentage of slaughtered cattle comes from Gonzanamá¸ the age range goes from 3 to 4 years; they are local; and a 23,5 % did not show any kind of pathology.